Postmodernistyczna powieść w oczach szkolnego polonisty: Postmodern novel in the eyes of high school Polish literature teacher - Kajtoch, Wojciech (Przegląd Wschodnioeuropejski, 2020)
The article is an analysis of the well-known and popular novel by Jerzy Sosnowski – “Apocrypha of Aglaya”. Although the problem of the unusual complexity of the story and the mystery of the sense within it is usually raised, the author of the article believes that the work can be examined with simple analytical tools, without resorting to analytical instruments more complex than those used at school. Obviously “Apocrypha of Aglaya” draws on various traditions and conventions, but it is generally based on known plot patterns. However, it is original and valuable, it contains important statements about the modern condition of man, without ceasing to be a romance and a thriller. The article is methodologically structuralist and opposes postmodern research trends.